Pengaruh Faktor Theory of Planned Behavior terhadap Kepatuhan Wajib Pajak Orang Pribadi: (Studi Kasus pada KPP Pratama Maumere) - Desy Purnamasari; Andreas Rengga; Konstantinus Pati Sanga (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This research aimed to analyze the influence of the theory of planned behavior on individual taxpayer compliance. The factors being investigated include behavioral attitudes, subjective norms, perceived behavioral control, and moral obligations. The research was a quantitative one. The population under research comprised all active taxpayers at the Maumere Pratama Tax Office, totaling 40,544 taxpayers. The sample size for this research was determined to be 100 taxpayers using the Slovin formula. Data collection was conducted by distributing questionnaires to respondents, and the research instrument utilized a Likert scale. The data analysis technique used a multiple linear regression analysis. model with the help of the SPSS 25 program. The research's results.showed that partially,behavioral attitudes, subjective norms, and behavioral control do not affect taxpayer compliance.However, moral obligations do affect taxpayer compliance.Additionally,it was found that behavioral attitudes, subjective norms, behavioral control,and moral obligations collectively affect taxpayer compliance.